Perpendicular photography of the reading of a measuring tape - Temples of India Project Team (Jio Institute, 2024)
Perpendicular photography of the reading of a measuring tape at heights that were difficult to access, Harshnath Temple Complex, Sikar district, Rajasthan. (Image Courtesy: Ar. Sumit Aher)